(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article scientifically analyzes musical heritage samples belonging to the Uzbek people that are preserved in the Russian Federation, specifically at the M.I.Glinka All-Russian Museum Association of Musical Culture. The work focuses on A.F.Eichhorn’s collection of musical instruments from Central Asian peoples, which he assembled while active in Turkestan. It details the history of its formation, its preservation status within the museum, and specifically highlights the ethnographic, art-historical, and cultural significance of Uzbek musical instruments. The article also highlights the contributions of musicologists such as V.M.Belyayev to the study of this heritage. It further illuminates the processes of documenting Uzbek traditional music through the collaborative efforts of museums and scientific institutions.